Fourteenth International Conference on Quality Control by Artificial Vision 2019
DOI: 10.1117/12.2521752
|View full text |Cite
|
Sign up to set email alerts
|

Calibration for polarization filter array cameras: recent advances

Abstract: A Polarization Filter Array (PFA) camera is an imaging device capable of analyzing the polarization state of light in a snapshot way. These cameras exhibit spatial variations, i.e. nonuniformity, in their response due to optical imperfections introduced during the nanofabrication process. Calibration is done by computational imaging algorithms to correct the data for radiometric and polarimetric errors. In this paper, we review existing calibration procedures, and show a practical implementation result of one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…There are a variety of different calibration techniques such as single-pixel calibration (Powell and Gruev, 2013), super-pixel calibration (Powell and Gruev, 2013;Lane et al, 2022), and more complex calibration techniques based on super-pixel calibration (e.g., Chen et al, 2015;Zhang et al, 2016). Giménez et al (2019Giménez et al ( , 2020 reviewed different calibration methods for division-of-focal-plane polarimeters. They found that the super-pixel calibration method performs well and that more complex calibration methods do not improve the calibration results significantly.…”
Section: Polarization Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a variety of different calibration techniques such as single-pixel calibration (Powell and Gruev, 2013), super-pixel calibration (Powell and Gruev, 2013;Lane et al, 2022), and more complex calibration techniques based on super-pixel calibration (e.g., Chen et al, 2015;Zhang et al, 2016). Giménez et al (2019Giménez et al ( , 2020 reviewed different calibration methods for division-of-focal-plane polarimeters. They found that the super-pixel calibration method performs well and that more complex calibration methods do not improve the calibration results significantly.…”
Section: Polarization Calibrationmentioning
confidence: 99%
“…The polarization-resolving cameras of specMACS can be classified as division-of-focal-plane polarimeters. There are a variety of different calibration techniques for division-of-focal-plane polarimeters, which have been reviewed by Giménez et al (2019Giménez et al ( , 2020. Lane et al (2022) for example calibrated the monochrome version of the polarization-resolving cameras from the same manufacturer as our cameras; however they did not provide an absolute calibration.…”
Section: Introductionmentioning
confidence: 99%
“…Number of acquisitions needed, along with the selection of the angle of analysis have been previously discussed by Tyo et al 14 Angles could differ from the ones used to calculate the Stokes vector in Eq. 2, and polarization elements do not need to be ideal, thus the polarimeter has to be polarimetrically calibrated [15][16][17] by estimating W. Afterward, S can be deduced by an inversion procedure, and polarization properties of light beams like Angle Of Linear Polarization (AOLP), Degree Of Polarization (DOP), or ellipticity, can be derived from the Stokes vector.…”
Section: Polarization Imaging Modelmentioning
confidence: 99%
“…16 Spatial calibration procedure is thus necessary to compensate for these nonuniformities. 17,18 We believe that this step is crucial for numerous applications. The uncalibrated camera values could lead to false contrasts or large errors when computer vision algorithms are applied, e.g., material inspection, shape from polarization, index of refraction retrieval, or illuminant direction estimation.…”
Section: Introductionmentioning
confidence: 99%